Telemedicine Solution using Django - Shivam; Ajay Kr. Dhiman; Shivam Gupta; Shashwat Rai; Swati Sharma (International Journal of Engineering and Management Research, 2020)
The average person usually don’t have much information about diseases related to symptoms they have and which doctor to visit for that disease. This causes a lot of wastage of time and money because they have to search doctor by doctor to get the right doctor and get an appointment with that doctor. Also not all doctors treat all diseases, this means just knowing your disease is not enough. Through this telemedicine solution we have tried to mitigate the inefficiency and delays in the system. Patients can get a basic idea of the possible disease they might have and a list of doctors suited to cure this disease is given as output to the patient. Then the patient can connect with doctors on a website.